QUALITY OF SHARIA GOVERNANCE STRUCTURE ON SOCIAL PERFORMANCE IN INDONESIAN ISLAMIC BANKING - Iryani, Lia Dahlia; Wahyudiono, Bambang (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This research aimed to examine empirically the effect of the performance of Islamic Bank on sharia governance in Indonesia. The social performance of the Islamic Bank was measured by qordhul hasan and micro finance, and sharia governance (SG) was measured by the proportion of the independent board of commissioners, board size, audit committee and sharia supervisory board. The data in this study were secondary data from Islamic Banking Financial Report (IBFR) of 2012-2016. This research applied quantitative approach with the panels of data regression using E-views 9.0 software. Data analysis was conducted by using factor analysis. The test result showed that the direct effect of SG on performance was 0.323 significant because it had a value of t count of 11.96 or a value of probability of (0,000) alpha 5%. The positive coefficient showed that SG was able to improve performance while the highest loading values that reflected SG (TKS) was X3 (number of KA members) of 0.934, and X4 (number of KA meetings in a year) of 0.880. The loading value of X5 was the number of DPS of 0.445 while the value of loading X2 (the number of DK meetings in 1 year) was 0.319